Comparison of the effectiveness of nsaids monotherapy and combination therapy with platelet-rich plasma in patients with osteochondrosis of the cervical spine - Shuhtin, V. V.; Leszczynskiy, M. V.; Badyin, I. Uy. (Journal of Education, Health and Sport, 2015)
Shuhtin V. V., Leszczynskiy M. V., Badyin I. Y. Сравнение эффективности монотерапии нпвс и комбинированной терапии с применением плазмы обогащенной тромбоцитами у больных остеохондрозом шейного отдела позвоночника = Comparison of the effectiveness of nsaids monotherapy and combination therapy with platelet-rich plasma in patients with osteochondrosis of the cervical spine. Journal of Education, Health and Sport. 2015;5(10):269-274. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32888 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2810%29%3A269-274 https://pbn.nauka.gov.pl/works/663587 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2015. Revised 05.09.2015. Accepted: 20.10.2015. УДК: 616.711.1-018.3-002.28-057:656.13]-092-08 Сравнение эффективности монотерапии НПВС и комбинированной терапии с применением плазмы обогащенной тромбоцитами у больных остеохондрозом шейного отдела позвоночника Comparison of the effectiveness of NSAIDs monotherapy and combination therapy with platelet-rich plasma in patients with osteochondrosis of the cervical spine ¹В. В. Шухтин, ²М. В. Лещинский, 1И. Ю. Бадьин V. V. Shuhtin, M. V. Leszczynskiy, I. Y. Badyin ¹ГП «Украинский научно-исследовательский институт медицины транспорта» ²КУ «Одесский областной клинический медицинский центр» Ukrainian Research Institute for Medicine of Transport Odessa Regional Clinical Medical Center Abstract According to numerous scientific data, the use of PRP accelerates the healing process in a variety of tissues. PRP is 100% biocompatible, safe and does not carry the risk of infection of the patient obtained from the patient’s own plasma. We studied the possibility of increasing the effectiveness of treatment of patients with osteochondrosis of the cervical spine, through the use in treatment of platelet-rich plasma. The article presents some results of local therapy with the use of platelet-rich plasma. Keywords: PRP-therapy, low back pain, platelet-rich plasma. Реферат По многочисленным научным данным, применение PRP ускоряет процессы заживления в самых разнообразных тканях. PRP на 100 % биосовместима, безопасна и не несет риска заражения пациента, получена из собственной плазмы пациента. Авторы изучили возможность повышения эффективности лечения пациентов, страдающих остеохондрозом шейного отдела позвоночника, посредством применения в комплексном лечении плазмы обогащенной тромбоцитами. В статье приведены некоторые результаты применения локальной терапии с использованием плазмы обогащенной тромбоцитами. Ключевые слова: PRP-терапия, остеохондроз, плазма обогащенная тромбоцитами.